Salter-Harris Type II Traumatic Separation of the Epiphyseal Cartlage Plate: A Report of Two Cases - Hirakawa, Kunitsugu; Nakamura, Tatsuhiko; Takata, Naohumi (Orthopedics & Traumatology, 1989)
Two cases of Salter-Harris Type II separation of the epiphyseal cartilage plate were treated at our hospital. Case 1. A 6-year-old boy fell from a swing and injured his left knee. Radiographs showed a Type II fracture of the distal femoral epiphysis with anterior displacement. Manipulative reduction was attemped and immobilization was applied with a plaster cast to the flexed leg. Case 2. A 13-year-old boy injured his right ankle while playing Judo. Radiographs showed a Type II fracture of the distal tibial epiphysis with posterior displacement, together with a spiral fracture of the lower fibula. Manipulative reduction was attempted and a plaster cast immobilization was applied. These two cases were treated conservatively with satisfactory results.